62.9k views
2 votes
Simplify the expression completely:

3(1+2(8-5))-(1+1)^2

2 Answers

3 votes

Answer:

8

Explanation:

Using PEMDAS to solve

Parentesis

Exponents

Multiplication

Division

Addition

Subtraction

:) hoped it helped

User Canhazbits
by
5.5k points
4 votes

Answer: 17

Explanation:

PEMDAS or wutever your teacher taught u

3(1+2(8-5))-(1+1)^2

Solve from the most inner parenthesis

8 - 5 = 3

3 x 2 = 6

6 + 1 = 7

7 x 3 = 21

Next solve the other part

1+1 = 2

2^2 = 4

Now put these two together

21-4 = 17

User Nextzeus
by
5.3k points